Disclosing a dementia diagnosis: what do patients and family consider important?. (August 2014) - Mastwyk, Maree; Ames, David; Ellis, Kathryn A.; Chiu, Edmond; Dow, Briony
ABSTRACT Background: The literature available on the format of the feedback session following assessment of memory impairment is minimal. This study explored how this information should be presented from the perspective of patients and their families. Methods: Thirty-two semi-structured interviews were conducted with memory clinic patients and their carer at the clinic visit that followed the feedback session, to ask: what they recalled, what they found helpful, and what they thought was the best way to disclose a diagnosis of dementia. A second interview was conducted with 14 patient/carer dyads at their next appointment. Results: Recall of information from the feedback session was variable. Most respondents (76% of patients; 66% of carers) thought that a direct approach was best when informing the patient of a dementia diagnosis, and that both written information and compassion demonstrated by the doctor were helpful. Opinions on whether all the information should be given at once or in stages were divided. Conclusions: The current format of the feedback session needs revision to improve recall. Patients and their families want a direct approach to be used by a supportive and professional doctor with an opportunity to ask questions. They want the support of a family member or friend when they are told of their diagnosis and they would like a written summary to refer to afterwards.